2013
DOI: 10.1128/aac.01675-12
|View full text |Cite
|
Sign up to set email alerts
|

A Reprofiled Drug, Auranofin, Is Effective against Metronidazole-Resistant Giardia lamblia

Abstract: Giardiasis is one of the most common causes of diarrheal disease worldwide. Treatment is primarily with 5-nitro antimicrobials, particularly metronidazole. Resistance to metronidazole has been described, and treatment failures can occur in up to 20% of cases, making development of alternative antigiardials an important goal. To this end, we have screened a chemical library of 746 approved human drugs and 164 additional bioactive compounds for activity against Giardia lamblia. We identified 56 compounds that ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
117
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 136 publications
(124 citation statements)
references
References 42 publications
5
117
0
Order By: Relevance
“…Thus, at present our understanding of the thioredoxin system in G. lamblia remains incomplete as there is no evidence for any protein that shuttles electrons from TrxR to peroxiredoxin or any other protein. It was clearly demonstrated that G. lamblia TrxR exerts disulphide reductase activity (Tejman-Yarden et al 2013;Leitsch et al 2016) but whether it functions as a true TrxR remains unclear. Interestingly, the impact of TrxR activity seems to be rather limited because strong overexpression of the enzyme had only little ATP-dependent RNA helicase p47, putative GL50803_16376…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, at present our understanding of the thioredoxin system in G. lamblia remains incomplete as there is no evidence for any protein that shuttles electrons from TrxR to peroxiredoxin or any other protein. It was clearly demonstrated that G. lamblia TrxR exerts disulphide reductase activity (Tejman-Yarden et al 2013;Leitsch et al 2016) but whether it functions as a true TrxR remains unclear. Interestingly, the impact of TrxR activity seems to be rather limited because strong overexpression of the enzyme had only little ATP-dependent RNA helicase p47, putative GL50803_16376…”
Section: Discussionmentioning
confidence: 99%
“…In light of its important function as the reducing enzyme of thioredoxin, TrxR has been repeatedly suggested to have considerable potential as a drug target for antigiardial chemotherapy (Tejman-Yarden et al 2013;Watkins and Eckmann, 2016). Comparably little, however, is known about the components of the thioredoxin-mediated redox system in G. lamblia.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, previous studies have also demonstrated mutagenic, teratogenic, and other cytotoxic effects [7,8]. In addition Giardia strains have been developing resistance to MTZ in vivo and manifesting cross-resistance to other nitroimidazole analogues, which results in treatment failures in up to 20% of cases [8][9][10]. Early in the last decade, US Food and Drug Administration has approved the use of nitazoxanide (NIT) for treatment giardiasis.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, inhibition of a few inflammatory pathways and of various thiol redox enzymes makes AF, an optimal candidate for cancer therapy and for treatment of various parasitic and microbial infections in the frame of a more general "drug repositioning strategy". For instance, relevant therapeutic actions were reported for AF toward Schistosoma japonicum (Song et al, 2012), Giardia lamblia (Tejman-Yarden et al, 2013) and Entamoeba histolytica (Debnath et al, 2012). In addition, four clinical trials were started against various cancer types and are still ongoing.…”
Section: Introductionmentioning
confidence: 99%